2020
DOI: 10.1111/jonm.13124
|View full text |Cite
|
Sign up to set email alerts
|

Acute stress disorder, coping self‐efficacy and subsequent psychological distress among nurses amid COVID‐19

Abstract: Health care professionals, particularly nurses, are considered a vulnerable group to experience acute stress disorder (ASD) and subsequent psychological distress amid COVID-19 pandemic. This study aims to establish the prevalence of acute stress disorder and predictors of psychological distress among Jordanian nurses. Methods: A quantitative, cross-sectional, descriptive and comparative design was used. Data were collected using a Web-based survey. A total of 448 Jordanian nurses (73% females) completed and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
242
1
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(281 citation statements)
references
References 67 publications
(95 reference statements)
27
242
1
11
Order By: Relevance
“…In a study during the H1N1 outbreak, hospital staff who were in their 20's had greater anxiety about becoming infected than did older staff ( 103 ). During COVID-19, HCW who were younger were more likely to experience higher levels of post-traumatic stress symptoms, depression, anxiety, and acute stress compared to older HCW ( 23 , 26 28 , 30 , 32 , 42 , 49 , 54 , 55 , 57 , 61 , 65 , 71 , 75 , 78 , 89 , 90 , 117 , 118 , 121 , 123 , 127 , 131 , 149 , 153 , 154 ). In contrast, eight studies conducted during COVID found that HCW who were older were at greater risk of experiencing higher levels of psychological distress ( 40 , 66 , 86 , 95 , 102 , 114 , 122 , 132 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study during the H1N1 outbreak, hospital staff who were in their 20's had greater anxiety about becoming infected than did older staff ( 103 ). During COVID-19, HCW who were younger were more likely to experience higher levels of post-traumatic stress symptoms, depression, anxiety, and acute stress compared to older HCW ( 23 , 26 28 , 30 , 32 , 42 , 49 , 54 , 55 , 57 , 61 , 65 , 71 , 75 , 78 , 89 , 90 , 117 , 118 , 121 , 123 , 127 , 131 , 149 , 153 , 154 ). In contrast, eight studies conducted during COVID found that HCW who were older were at greater risk of experiencing higher levels of psychological distress ( 40 , 66 , 86 , 95 , 102 , 114 , 122 , 132 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies examined how perceptions of control were associated with distress among HCW ( Table 2 ). In eight studies, higher self-efficacy was associated with lower anxiety, depression, distress, and lower levels of fear about SARS and post-traumatic stress symptoms during the COVID-19 and SARS outbreaks, respectively ( 10 , 35 , 68 , 72 , 90 , 105 , 123 , 150 ). Conversely, feeling a loss of control was associated with greater distress ( 148 ) during the SARS outbreak in Hong Kong.…”
Section: Resultsmentioning
confidence: 99%
“…Amidst emerging research, which largely focuses on the emotional hardship and negative experiences nurses faced during COVID-19 ( Han et al., 2020 ; Shahrour & Dardas, 2020 ; Shreffler et al., 2020 ), our study provides an additional angle that includes positive elements of strength, learning, and resilience. Although the uncertainty of the situation and lack of a clear endpoint represented one of the toughest challenges for nurses, confronting these difficult experiences enabled them to realize their capacity to adapt to adversity.…”
Section: Discussionmentioning
confidence: 99%
“…Frontline nurses also deserve particular attention. Of 28 included investigations about postpandemic PTSD prevalence among healthcare workers, 6 studies [29,49,60,68,81,83] focused particularly on frontline nurses and found a high prevalence of PTSD, which indicates relative vulnerability of this group to develop postpandemic PTSD. Uncomfortable working environments including the long-term use of personal protective equipment, intense and often overloaded work intensity of an extended duration because of severe pandemic conditions, a lack of understanding and specific drugs to fight the disease, and unavoidable psychological shock that is caused by the demise of infected patients all contribute to the high prevalence of PTSD among both frontline healthcare workers and frontline nurses.…”
Section: Psychological Responsementioning
confidence: 99%